2021
DOI: 10.3390/jcm10030464
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Use of Arterial Doppler Waveform Classifications in Clinical Routine to Describe Lower Limb Flow

Abstract: Background: Characterisation of arterial Doppler waveforms is a persistent problem and a source of confusion in clinical practice. Classifications have been proposed to address the problem but their efficacy in clinical practice is unknown. The aim of the present study was to compare the efficacy of the categorisation rate of Descotes and Cathignol, Spronk et al. and the simplified Saint-Bonnet classifications. Methods: This is a multicentre prospective study where 130 patients attending a vascular arterial ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
0
10
0
3
Order By: Relevance
“…Classification systems are a very useful tool in improving the homogeneity of Doppler flow waveform characterization (38)(39)(40). The simplified Saint-Bonnet classification system was used in the present study as recommended by professors of the French College of Vascular Medicine (13,19) the SFMV/SCVE consensus (14), and a study has shown that it yields superior categorization rates by comparison with other classification systems (41).…”
Section: Discussionmentioning
confidence: 99%
“…Classification systems are a very useful tool in improving the homogeneity of Doppler flow waveform characterization (38)(39)(40). The simplified Saint-Bonnet classification system was used in the present study as recommended by professors of the French College of Vascular Medicine (13,19) the SFMV/SCVE consensus (14), and a study has shown that it yields superior categorization rates by comparison with other classification systems (41).…”
Section: Discussionmentioning
confidence: 99%
“…This Saint-Bonnet classification is the classification taught in France for the past 2 years for the vascular residents but which is not part of the continuing education program for practicing physicians ( 8 ). It contains 13 categories that allow a better classification of the DW than other classification ( 11 , 15 ). In the present study, the reliability is considered as weak to moderate (κ = 0.546 [0.544–0.547], p < 0.005) in vascular caregivers unfamiliar with this Saint-Bonnet classification.…”
Section: Discussionmentioning
confidence: 99%
“…The simplified Saint-Bonnet classification was proposed in 2017, comprises eight types, and allows considering the continuous character of the flow (mentioned with the abbreviation CF) for 13 total categories. The various types are described as follows in the original publication ( 8 , 11 ):…”
Section: Methodsmentioning
confidence: 99%
“…There is extensive evidence supporting the relationship between Doppler waveform contours with the presence and extent of PAD. The contours of the Doppler waveform change with PAD progression, from normal, triphasic waveforms towards biphasic or monophasic ones in the case of high degree stenosis [ 16 ].…”
Section: Clinical Relevance Of Mac In Patients With Padmentioning
confidence: 99%